Implementation of The Khiyar Concept in Shopee Barokah's Free Return Guarantee Mechanism - Danik Purnomo; Suci Anisa Putri; Yuhana Badriatussholikhah; Muhammad Hamim Arriza (Journal of Sharia Economic Law, 2026)
The expansion of Sharia-based e-commerce has given rise to consumer protection mechanisms, such as free return guarantees, that require examination from the perspective of Islamic commercial law. This study aims to analyze the implementation of the khiyar concept in Shopee Barokah’s Free Return Guarantee mechanism from the perspectives of classical Islamic jurisprudence (fiqh al-muʿāmalāt) and contemporary regulatory frameworks. This research employs a normative library approach by examining classical fiqh literature, DSN–MUI fatwas, and Shopee Barokah’s internal regulations and policies, with data analyzed descriptively to assess their conformity with Sharia principles. The findings demonstrate that the Free Return Guarantee mechanism substantively reflects the implementation of khiyar al-sharṭ through a specified return period, khiyar al-ʿayb through remedies for defective or damaged goods, and khiyar al-ruʾyah by allowing buyers to inspect goods after delivery and rescind transactions when appropriate. These mechanisms are consistent with the principles of justice, transparency, and consumer protection in Islamic economic law. This study contributes by integrating classical fiqh, DSN–MUI fatwas, and Sharia-compliant e-commerce regulations into a unified framework for analyzing digital return guarantees. However, the study is limited to normative analysis, and future research should incorporate empirical approaches to evaluate the practical implementation and effectiveness of khiyar mechanisms in digital marketplaces.